The Peruvian university nowadays critical vision from the management - Alvarado Oyarce, Otoniel (2012)
This article, essay-comment, is intended to analyze some of the critical features that the Peruvian university is goingthrough, during the last decades, as a product of the empirical observation of the author during nearly forty years ofuniversity teaching and the contributions of many scholars about the subject, who from different and varied approaches,reach coinciding conclusions on the dangerous forecast of the university development decline of our country and what isworse, that it does not contribute significantly to a comprehensive development, which is its raison d ' être.